Digital multimedia - Chapman, Nigel; Chapman, Jenny (John Wiley & Sons, 2009)
"This book is the best-selling core text for undergraduate and masters courses in the exciting discipline of multimedia, combining a broad and deep account of technology with an inside understanding of multimedia content and its practical application. Beginning with an overview of the nature of multimedia and digital representations, it continues with chapters devoted to each media type, detailing how they are represented in digital form and how they are created and manipulated on computers. Later chapters describe how media may be combined and how scripting may be used to add interactivity. Whole chapters are devoted to visual design and accessibility, and to how multimedia may be delivered over the Internet. Each chapter includes key point summaries and exercises. An extensive glossary of important terms is provided."